Effect of Moxibustion on Testosterone Secretion and Apoptosis of Spermatogenic Cells in Aging Rats. (24th October 2019) - Yao, Chongjie; Zhao, Chen; Zhang, Shuyan; Liu, Shimin
Abstract : Analysis of androgen secretion and sperm production was conducted in the testis to investigate the efficacy of moxibustion on testicular function in aging rats. Male Sprague–Dawley rats were randomly divided into the aging group ( N  = 8), the mild-warm moxibustion group ( N  = 8), and the youth control group ( N  = 8). Rats in the mild-warm moxibustion group (MWMG) were exposed to mild-warm moxibustion at the Zusanli (ST36) and Shenshu (BL23) acupuncture points daily, from the age of 12 months until the age of 24 months. After the intervention, testicular tissue was harvested from all rats across groups. Changes in testicular structure were examined by hematoxylin and eosin (H&E) stain. Detection of the apoptosis of spermatogenic cells was performed by the TUNEL assay. Testosterone level in the testis was analyzed by the ELISA assay, and the expression of Bax, Bcl-2, and androgen receptor (AR) in the testis was evaluated by immunohistochemistry. AR expression analysis was subsequently performed by the western blotting assay, and the detection of telomerase activity of the testis and the expression of Bax, Bcl-2, and AR mRNA were performed by real-time PCR. Compared with the youth controls, telomerase activity in the testis, testosterone levels, expression of AR, and expression of antiapoptosis factor Bcl-2 protein and mRNA were significantly decreased (P < 0.01 ) in the aging group. Spermatogenic cell apoptosis (P < 0.01 ) and proapoptotic factor Bax expression were significantly increased (P < 0.01 ) in the aging rats compared with the youth control group. The MWMG exhibited significant increases in testicular telomerase activity, testosterone level, AR expression, and antiapoptosis factor Bcl-2 expression (P < 0.05 or P < 0.01 ) compared with the aging group. In this experimental group, spermatogenic apoptosis was inhibited (P < 0.01 ) and proapoptotic factor Bax expression significantly reduced (P < 0.01 ). Mild-warm moxibustion can inhibit reproductive senescence by improving telomerase activity, improving AR expression, restoring testosterone, and inhibiting spermatogenic apoptosis via regulation of Bcl-2/Bax.